THE EFFECTIVENESS OF PICTURES IN ENHANCE WRITING SKILL OF SENIOR HIGH SCHOOL STUDENTS - Sakkir, Geminastiti (Universitas Negeri Makassar, 2020)
Abstract. The purpose of this research was to know the effectiveness of pictures in writing class of senior high school students. It employed a quantitative method using the quasi-experimental design. The subject of the research was the third year students of on senior high school in Sidrap Regency, South Sulawesi, Indonesia. The total number of population is 100 students which are distributed in 5 classes. Each class consists of 20 students. The sampling technique used in this research is cluster random sampling. The instrument was a writing test to obtain data on the students’ writing achievement through the pictures. Based on the result the researcher concluded that the pictures enhance the writing skill of senior high schools’ students.